A kind of preparation method of lactide

By using two-step reaction and green environmentally friendly catalysts in the lactide preparation process, combined with specific catalyst preparation methods and reaction steps, the problems of low lactide yield and high free acid content in the product in the prior art are solved. , high yield and high purity preparation of lactide is achieved.

CN119019358BActive Publication Date: 2025-02-14SHOUGUANG GOLDEN FAR EAST MODIFIED STARCH CO LTD +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411514170.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The prior art has waste of materials and catalysts when preparing lactide, resulting in low yield of lactide and high free acid content in the product.

Method used

The lactide is prepared by a two-step reaction using a green and environmentally friendly catalyst, and through specific catalyst preparation methods and reaction steps, including polycondensation and depolymerization reaction, combined with purification and post-treatment steps, to improve the yield and purity of lactide.

Benefits of technology

It improves the yield and purity of lactide, reduces the waste of materials and catalysts, reduces the free acid and moisture content in the product, and reduces the production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a method for preparing lactide, belonging to the technical field of lactide; the preparation method comprises polycondensation reaction, depolymerization reaction, purification and post-treatment; in the polycondensation reaction, L-lactic acid and a catalyst are placed in a polycondensation device for polycondensation reaction; the preparation method of the catalyst comprises graphene pretreatment, dispersion treatment, modification treatment and compounding; in the dispersion treatment, the pretreated graphene is placed in an ethanol solution, lauramide propylamine oxide is added, and stirring is performed, after the stirring is completed, 2,6-diaminopyridine is added, the temperature is increased to 80-84°C at a rate of 0.7-1.4°C / min, the temperature is kept and stirred for 4.3-4.6h, and then L-glutamine is added, the temperature is kept and stirred for 4.3-4.8h, and dispersed graphene is obtained after the stirring is completed; the method of the invention is used to prepare a lactide product, the lactide yield is high, and the free acid and water contents in the lactide product are low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lactide, and particularly relates to a method for preparing lactide. Background Art

[0002] Polylactic acid is a thermoplastic aliphatic polyester. Its raw materials come from renewable plant fibers, corn, agricultural and sideline products, etc. It has good biodegradability and can be completely degraded into carbon dioxide and water after use. It is green and environmentally friendly. Polylactic acid has excellent mechanical properties, similar to petroleum-based polypropylene plastics. It can replace PP and PET plastics in some fields. At the same time, polylactic acid material has good gloss, transparency, feel and certain antibacterial properties. It is widely used in medicine, electronics, materials and other fields.

[0003] The preparation methods of polylactic acid include a one-step method and a two-step method. The one-step method uses lactic acid as a raw material to directly synthesize polylactic acid. The polylactic acid synthesized by this method has a small molecular weight, poor mechanical properties, and low application value. At present, the commonly used method for producing polylactic acid is a two-step method, which is to dehydrate lactic acid under the action of a catalyst to generate oligomeric lactic acid, and then the oligomeric lactic acid is depolymerized to generate lactide, and the lactide monomer is ring-opening polymerized to obtain polylactic acid; that is, polylactic acid is prepared by the process of lactic acid-lactide-polylactic acid;

[0004] It can be seen that lactide is an important intermediate for preparing polylactic acid through a two-step process, which is of great significance for the production of high-quality polylactic acid.

[0005] CN114105936A discloses a method for preparing lactide from lactic acid, which uses lactic acid as a raw material, and then performs polycondensation and depolymerization reactions, wherein the polycondensation and depolymerization reactions are both performed in the presence of a catalyst, and the catalyst is preferably at least one selected from stannous octoate, ZnO and creatinine;

[0006] The lactide product obtained by the method of the present invention has a maximum yield of 97%, but the yield is still poor and the utilization rate of raw materials is low.

[0007] CN118026990A discloses a method for preparing lactide, specifically disclosing the depolymerization of oligomeric lactic acid under the action of a mesoporous molecular sieve-supported zinc catalyst to produce lactide, wherein the catalyst is prepared by mixing a self-made mesoporous molecular sieve SBA-15 powder with a dilute hydrochloric acid solution of zinc nitrate, drying, and then calcining; the self-made mesoporous molecular sieve SBA-15 powder is prepared by mixing a surfactant P123 with hydrochloric acid and ultrapure water, then adding tetraethyl orthosilicate, continuously and vigorously stirring, standing for crystallization for 72 hours, cooling, filtering, washing, and drying, and finally calcining at 550°C to remove the template agent to obtain a white powder, namely SBA-15;

[0008] The patented preparation method has a green and environmentally friendly catalyst and increases the lactide yield to 89%, but the content of free acids such as lactic acid is relatively high.

[0009] In addition, the prior art has the following problems in the process of preparing lactide by the two-step method: during the depolymerization process, since the oligomeric lactic acid continues to condense, it is difficult to depolymerize at the original depolymerization temperature after reaching a certain degree of polymerization, resulting in a large amount of material waste. At the same time, the frequent discharge of depolymerization residues leads to a waste of catalysts and reduces the yield of lactide.

[0010] Therefore, providing a method for preparing lactide, adopting a two-step reaction, using a green and environmentally friendly catalyst, avoiding waste of materials and catalysts, increasing the yield of lactide, and reducing the free acid content of the product are technical problems that need to be urgently solved in the prior art. Summary of the invention

[0011] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing lactide, which adopts a two-step reaction, uses a green catalyst, avoids waste of materials and catalysts, has a high yield of lactide, and has a low free acid content in the product.

[0012] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0013] A method for preparing lactide comprises the following steps:

[0014] 1. Polycondensation

[0015] 100 wt% L-lactic acid is added to a polycondensation device fixed with a catalyst, the temperature of the polycondensation device is increased to 117-122°C, the vacuum degree is controlled to be 7960-8040Pa, a polycondensation reaction is carried out, the time of the first polycondensation reaction is 1.8-2.2h, after the first polycondensation reaction is completed, the temperature of the polycondensation device is increased to 156-163°C at a rate of 0.8-1.3°C / min, the vacuum degree is controlled to be 2980-3020Pa, a secondary polycondensation reaction is carried out, the time of the secondary polycondensation reaction is 2.8-3.3h, after the secondary polycondensation reaction is completed, a polycondensation reactant is obtained;

[0016] The polycondensation device is one of a stirred tank type, a falling film type or a scraped film type reaction device;

[0017] The amount of the catalyst added is 0.55-0.60% of the dry mass of L-lactic acid;

[0018] The method for preparing the catalyst comprises the following steps:

[0019] a. Graphene pretreatment

[0020] The graphene is placed in a nitric acid solution for ultrasonic dispersion treatment, the ultrasonic time is 23-28 minutes, the ultrasonic power is 175-184W, and the ultrasonic frequency is 28-32kHz. After the ultrasonic dispersion is completed, the temperature is increased to 62-67°C, and stirred at 240-260rpm for 2.7-3.2h. After filtering and washing, it is dried at 83-88°C for 5.8-6.2h to obtain pretreated graphene;

[0021] The particle size of the graphene is 120-140 nm;

[0022] The mass concentration of the nitric acid solution is 22-25%;

[0023] The mass ratio of the graphene to the nitric acid solution is 8.0-8.4:73-80;

[0024] b. Distributed processing

[0025] The pretreated graphene is placed in an ethanol solution, lauramide propylamine oxide is added, the temperature is raised to 52-57°C for stirring, the stirring speed is controlled to 310-326rpm, the stirring time is 1.0-1.5h, after the stirring is completed, 2,6-diaminopyridine is added, the temperature is raised to 80-84°C at a rate of 0.7-1.4°C / min, the mixture is kept warm and stirred for 4.3-4.6h, and then L-glutamine is added, the mixture is kept warm and stirred for 4.3-4.8h, and after the stirring is completed, dispersed graphene is obtained;

[0026] The mass concentration of the ethanol solution is 24-28%;

[0027] The mass ratio of the pretreated graphene, ethanol solution, lauryl amide propyl amine oxide, 2,6-diaminopyridine, and L-glutamine is 7.3-7.7:96-105:0.72-0.77:11.0-11.5:10.0-10.3;

[0028] c. Modification treatment

[0029] The dispersed graphene is placed in an ethanol solution, stirred evenly, and then the temperature is raised to 33-38°C, and the modification liquid 1 is added at a speed of 488-510rpm, and the addition rate of the modification liquid 1 is controlled to be 0.50-0.54g / min. After the addition is completed, the reaction is kept warm for 27-33min, and 20-24wt% ammonia water is added to adjust the pH to 9.0-9.2, and then the modification liquid 2 is added, and the addition rate of the modification liquid 2 is controlled to be 0.22-0.29g / min. After the addition is completed, the reaction is continued to be stirred for 23.5-24.5h, and after centrifugal separation and washing, it is dried at -42 to -38°C for 9-12h to obtain modified graphene;

[0030] The mass concentration of the ethanol solution is 17-22%;

[0031] The mass ratio of the dispersed graphene, the ethanol solution, the modified liquid 1, and the modified liquid 2 is 4.0-4.4:127-132:19.6-20.3:3.8-4.2;

[0032] The modified liquid 1 is prepared by mixing tetraethyl orthosilicate and anhydrous ethanol, and the mass ratio of tetraethyl orthosilicate to anhydrous ethanol is 3.8-4.2:15.7-16.4;

[0033] The modified liquid 2 is prepared by mixing sorbitan trioleate and 18-22wt% ethanol solution, and the mass ratio of sorbitan trioleate to 18-22wt% ethanol solution is 0.2:3.6-4.1;

[0034] d. Compound

[0035] The modified graphene is placed in a metal composite liquid, the temperature is increased to 30-35°C, and the mixture is stirred for 35-43 minutes. After the stirring is completed, the mixture is homogenized at a pressure of 3.4-3.7 MPa, a homogenization time of 4.0-5.0 minutes, and a homogenization frequency of 3 times. After the homogenization is completed, the temperature is increased to 57-62°C, and the mixture is stirred for 3.8-4.4 hours. After the stirring is completed, the mixture is separated and dried, and then placed in a calcination furnace for calcination. The mixture is heated to 254-265°C at a rate of 4.7-5.3°C / min, and the mixture is kept at the temperature for calcination for 18-23 minutes. The mixture is then heated to 506-513°C at a rate of 3.0-3.5°C / min, and the mixture is kept at the temperature for 4.0-4.5 hours. After the calcination is completed, the mixture is naturally cooled to room temperature to obtain a catalyst.

[0036] The mass ratio of the modified graphene to the metal composite liquid is 3.7-4.3:20-26;

[0037] The metal composite liquid is a mixed liquid of magnesium citrate, zirconium chloride and deionized water, and the mass ratio of the magnesium citrate, zirconium chloride and deionized water is 4.4-4.8:5.0-5.3:100.

[0038] 2. Depolymerization reaction

[0039] The polycondensation reactants are fed into a depolymerization device 1 fixed with a catalyst, and the depolymerization temperature is controlled to be 238-242°C and the vacuum degree is 992-1000Pa. After the material is depolymerized by 85%, the depolymerized material obtained after the depolymerization is completed is fed into a purification system, and the undepolymerized oligomers are transported to the polycondensation device. 100wt% L-lactic acid is continuously added to the polycondensation device. The amount of L-lactic acid added is 85-90% of the mass of L-lactic acid in the polycondensation reaction step, and the undepolymerized oligomers returned to the polycondensation device are added. The oligomers are mixed, the temperature is controlled at 117-122°C, the vacuum degree is 7960-8040Pa, and a polycondensation reaction is carried out for 1.8-2.2h. After the polycondensation reaction is completed, the polycondensation device is heated to 156-163°C at a rate of 0.8-1.3°C / min, the vacuum degree is controlled at 2980-3020Pa, and a secondary polycondensation reaction is carried out for 2.8-3.3h to complete the secondary polycondensation reaction;

[0040] The depolymerization device 1 is one of a stirred tank device, a falling film device or a scraped film device;

[0041] The catalyst used in the depolymerization reaction is the same as the catalyst in the polycondensation reaction step, and the amount used is 0.55-0.60% of the dry mass of L-lactic acid in the polycondensation reaction step.

[0042] 3. Purification

[0043] The depolymerized material obtained after depolymerization is fed to a purification system, and the purification method is distillation purification. The bottom temperature of the distillation device is controlled to be 157-162°C, the vacuum degree is 495-503Pa, and the top reflux ratio is 1:2. The side-drawn product is cooled and granulated to obtain a polymerization-grade lactide product;

[0044] During the distillation and purification process, light components such as water, lactic acid, and M-lactide are discharged from the top of the tower. They can be returned to the polycondensation device and mixed with lactic acid to continue the polycondensation reaction, or they can be recycled separately.

[0045] 4. Post-processing

[0046] After the polycondensation device and the depolymerization device have been operated continuously for one week, the residue is discharged once, and the residue enters the degradation device for degradation. During the degradation process, nitrogen is filled for protection. The temperature is controlled at 200-206° C. under normal pressure, the stirring speed is 76-83 rpm, and the degradation time is 0.9-1.2 h. After the degradation step is completed, the residue is transferred to the depolymerization device 2 for depolymerization. The depolymerization temperature is controlled at 238-242° C. and the pressure is 992-1000 Pa. After the depolymerization material obtained by the depolymerization in the depolymerization device 2 is cooled, it is mixed with the depolymerization material obtained by the depolymerization in the depolymerization device 1 for purification, and the remaining residue is discharged;

[0047] The degradation device is one of a kettle stirring device, a falling film device or a scraping film device;

[0048] The depolymerization device 2 is one of a stirred tank device, a falling film device or a scraped film device.

[0049] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0050] 1. The present invention adopts a specific method to prepare the catalyst, using graphene as a catalyst carrier, dispersing the graphene, wherein 2,6-diaminopyridine can be grafted onto the graphene surface, and L-glutamine can also react and connect with 2,6-diaminopyridine, thereby expanding the interlayer spacing of the graphene and enhancing the dispersion performance of the graphene, which is more conducive to the loading of active metals and improving the catalytic activity. In the modification step, silicon dioxide and the dispersed graphene are in situ polymerized, combined with the composite step, the stability of the catalyst is enhanced, and the catalytic activity and long-lasting catalytic performance are guaranteed; at the same time, the same catalyst as in the polycondensation step is used in the depolymerization step, and the depolymerization is completed to obtain the depolymerized The material is purified to obtain a lactide product, which improves the purity and yield of the lactide product and reduces the impurities and moisture content; the undepolymerized material is returned to the polycondensation device to react with lactic acid again, so that the molecular weight of the polymer with a higher molecular weight is rearranged by reacting with lactic acid, and the molecular weight is reduced, which is conducive to smooth depolymerization at the subsequent temperature; before intermittent residue discharge, the oligomer with a higher degree of polymerization is appropriately degraded under nitrogen protection to reduce the degree of polymerization of the polymer in the residue, and subsequent depolymerization is performed to further improve the lactide yield, and then the residue is discharged, which improves the raw material utilization rate and the total yield of lactide, reduces the production cost of lactide, improves the product purity, and reduces the amount of residue discharged;

[0051] 2. The method of the present invention is used to prepare a lactide product, the lactide yield is 99.67-99.84%, the free acid mass content in the lactide product is 0.018-0.022%, the water mass content is 0.015-0.018%, and the lactide mass content is 99.885-99.897%;

[0052] 3. The catalyst prepared by the method of the present invention was used for continuous production, and the continuous production time was 960 hours. The yield of lactide was measured again, and it was 97.68-98.65%, the free acid mass content in the lactide product was 0.019-0.025%, the water mass content was 0.016-0.020%, and the lactide mass content was 98.487-99.098%. DETAILED DESCRIPTION

[0053] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.

[0054] Example 1

[0055] 1. Polycondensation

[0056] 100 wt% L-lactic acid is added to a polycondensation device fixed with a catalyst, the polycondensation device is a falling film reaction device, the temperature of the polycondensation device is increased to 120°C, the vacuum degree is controlled to be 8000Pa, a polycondensation reaction is carried out, the time of the first polycondensation reaction is 2.0 hours, after the first polycondensation reaction is completed, the temperature of the polycondensation device is increased to 160°C at a rate of 1.0°C / min, the vacuum degree is controlled to be 3000Pa, a secondary polycondensation reaction is carried out, the time of the secondary polycondensation reaction is 3.0 hours, after the secondary polycondensation reaction is completed, a polycondensation reactant is obtained;

[0057] The amount of the catalyst added is 0.58% of the dry mass of L-lactic acid;

[0058] The method for preparing the catalyst comprises the following steps:

[0059] a. Graphene pretreatment

[0060] 8.2 g of graphene was placed in a 23 wt % 76 g nitric acid solution for ultrasonic dispersion treatment, the ultrasonic time was 25 min, the ultrasonic power was 180 W, and the ultrasonic frequency was 30 kHz. After the ultrasonic dispersion was completed, the temperature was raised to 65 ° C, stirred at 250 rpm for 3.0 h, filtered out and washed, and dried at 85 ° C for 6.0 h to obtain pretreated graphene;

[0061] The particle size of the graphene is 130 nm;

[0062] b. Distributed processing

[0063] 7.5 g of pretreated graphene was placed in 100 g of 26 wt% ethanol solution, 0.75 g of lauryl amide propyl amine oxide was added, the temperature was raised to 54° C. and stirred, the stirring speed was controlled to 320 rpm, the stirring time was 1.2 h, after the stirring was completed, 11.3 g of 2,6-diaminopyridine was added, the temperature was raised to 82° C. at a rate of 1.0° C. / min, the mixture was kept warm and stirred for 4.5 h, and then 10.2 g of L-glutamine was added, the mixture was kept warm and stirred for 4.5 h, and dispersed graphene was obtained after the stirring was completed;

[0064] c. Modification treatment

[0065] 4.2 g of dispersed graphene was placed in 130 g of 20 wt% ethanol solution, and after stirring evenly, the temperature was raised to 35° C., 20.0 g of modified liquid 1 was added at a speed of 500 rpm, and the addition rate of modified liquid 1 was controlled to be 0.52 g / min. After the addition was completed, the reaction was kept warm for 30 min, 23 wt% ammonia water was added to adjust the pH to 9.1, and then 4.0 g of modified liquid 2 was added, and the addition rate of modified liquid 2 was controlled to be 0.25 g / min. After the addition was completed, the reaction was continued to stir for 24.0 h, centrifuged, washed, and dried at -40° C. for 10 h to obtain modified graphene;

[0066] The modified liquid 1 is prepared by mixing tetraethyl orthosilicate and anhydrous ethanol, and the mass ratio of tetraethyl orthosilicate to anhydrous ethanol is 4.0:16.0;

[0067] The modified liquid 2 is prepared by mixing sorbitan trioleate and 20wt% ethanol solution, and the mass ratio of sorbitan trioleate to 20wt% ethanol solution is 0.2:3.8;

[0068] d. Compound

[0069] 4.0g of modified graphene was placed in 23g of metal composite liquid, the temperature was raised to 32°C, and stirred for 40min. After the stirring was completed, homogenization was performed, the homogenization pressure was 3.6MPa, the homogenization time was 4.5min, and the homogenization times were 3 times. After the homogenization was completed, the temperature was raised to 60°C and stirred for 4.0h. After the stirring was completed, the mixture was separated and dried, and then placed in a calcination furnace for calcination. The temperature was raised to 260°C at a rate of 5.0°C / min, and the mixture was kept at this temperature for calcination for 20min. The temperature was then raised to 510°C at a rate of 3.3°C / min, and the mixture was kept at this temperature for 4.2h. After the calcination was completed, the temperature was naturally lowered to room temperature to obtain a catalyst.

[0070] The metal composite liquid is a mixed liquid of magnesium citrate, zirconium chloride and deionized water, and the mass ratio of the magnesium citrate, zirconium chloride and deionized water is 4.6:5.2:100.

[0071] 2. Depolymerization reaction

[0072] The polycondensation reactant is fed into a depolymerization device 1 fixed with a catalyst, the depolymerization device 1 is a scraping device, the depolymerization temperature is controlled to be 240°C, the vacuum degree is 996Pa, after the material is depolymerized by 85%, the depolymerized material obtained by depolymerization is fed to the purification system, the undepolymerized oligomers are transported to the polycondensation device, 100wt% L-lactic acid is continuously added to the polycondensation device, the amount of L-lactic acid added is 88% of the mass of L-lactic acid in the polycondensation reaction step, and mixed with the undepolymerized oligomers returned to the polycondensation device, the temperature is controlled to be 120°C, the vacuum degree is 8000Pa, a polycondensation reaction is carried out, the time of the first polycondensation reaction is 2.0h, after the first polycondensation reaction is completed, the polycondensation device is heated to 160°C at a rate of 1.0°C / min, the vacuum degree is controlled to be 3000Pa, a secondary polycondensation reaction is carried out, the time of the secondary polycondensation reaction is 3.0h, and the second polycondensation reaction is completed;

[0073] The catalyst used in the depolymerization reaction is the same as the catalyst in the polycondensation reaction step, and the amount used is 0.58% of the dry basis mass of the L-lactic acid in the polycondensation reaction step.

[0074] 3. Purification

[0075] The depolymerized material obtained after depolymerization is fed to a purification system, and the purification method is distillation purification. The bottom temperature of the distillation device is controlled to be 160° C., the vacuum degree is 500 Pa, and the top reflux ratio is 1:2. The side-drawn product is cooled and granulated to obtain a polymerization-grade lactide product;

[0076] During the distillation and purification process, light components such as water, lactic acid, and M-lactide are discharged from the top of the tower. They can be returned to the polycondensation device and mixed with lactic acid to continue the polycondensation reaction, or they can be recycled separately.

[0077] 4. Post-processing

[0078] After the polycondensation device and the depolymerization device have been running continuously for one week, the residue is discharged once, and the residue enters the degradation device for degradation. The degradation device is a kettle stirring device. During the degradation process, nitrogen is filled for protection. The temperature is controlled to be 204°C under normal pressure, the stirring speed is 80rpm, and the degradation time is 1.0h. After the degradation step is completed, the device is transferred to the depolymerization device 2 for depolymerization. The depolymerization device 2 is a scraping device. The depolymerization temperature is controlled to be 240°C and the pressure is 996Pa. After the depolymerization material obtained by the depolymerization in the depolymerization device 2 is cooled, it is mixed with the depolymerization material obtained by the depolymerization in the depolymerization device 1 for purification, and the remaining residue is discharged.

[0079] The lactide product was prepared by the method of Example 1, and the lactide yield was 99.84%, the free acid mass content in the lactide product was 0.018%, the water mass content was 0.015%, and the lactide mass content was 99.897%.

[0080] Example 2

[0081] 1. Polycondensation

[0082] 100 wt% L-lactic acid is added to a polycondensation device fixed with a catalyst, the polycondensation device is a scraping film reaction device, the temperature of the polycondensation device is raised to 117°C, the vacuum degree is controlled to be 7960Pa, a polycondensation reaction is carried out, the time of the first polycondensation reaction is 1.8 hours, after the first polycondensation reaction is completed, the polycondensation device is heated to 156°C at a rate of 0.8°C / min, the vacuum degree is controlled to be 2980Pa, a secondary polycondensation reaction is carried out, the time of the secondary polycondensation reaction is 3.3 hours, after the secondary polycondensation reaction is completed, a polycondensation reactant is obtained;

[0083] The amount of the catalyst added is 0.55% of the dry mass of L-lactic acid;

[0084] The method for preparing the catalyst comprises the following steps:

[0085] a. Graphene pretreatment

[0086] 8.0 g of graphene was placed in 73 g of 22 wt % nitric acid solution for ultrasonic dispersion treatment, the ultrasonic time was 23 min, the ultrasonic power was 175 W, and the ultrasonic frequency was 28 kHz. After the ultrasonic dispersion was completed, the temperature was raised to 62 ° C, stirred at 240 rpm for 2.7 h, filtered out and washed, and dried at 83 ° C for 6.2 h to obtain pretreated graphene;

[0087] The particle size of the graphene is 120 nm;

[0088] b. Distributed processing

[0089] 7.3 g of pretreated graphene was placed in 96 g of 24 wt% ethanol solution, 0.72 g of lauramide propylamine oxide was added, the temperature was raised to 52° C. and stirred, the stirring speed was controlled to 310 rpm, the stirring time was 1.0 h, after the stirring was completed, 11.0 g of 2,6-diaminopyridine was added, the temperature was raised to 80° C. at a rate of 0.7° C. / min, the mixture was kept warm and stirred for 4.3 h, and then 10.0 g of L-glutamine was added, the mixture was kept warm and stirred for 4.3 h, and dispersed graphene was obtained after the stirring was completed;

[0090] c. Modification treatment

[0091] 4.0 g of dispersed graphene was placed in 127 g of 17 wt% ethanol solution, and after stirring evenly, the temperature was raised to 33° C., 19.6 g of modified liquid 1 was added at a speed of 488 rpm, and the addition rate of modified liquid 1 was controlled to be 0.50 g / min. After the addition was completed, the reaction was kept warm for 27 min, 20 wt% ammonia water was added to adjust the pH to 9.0, and then 3.8 g of modified liquid 2 was added, and the addition rate of modified liquid 2 was controlled to be 0.22 g / min. After the addition was completed, the reaction was continued to stir for 23.5 h, and after centrifugal separation and washing, it was dried at -38° C. for 12 h to obtain modified graphene;

[0092] The modified liquid 1 is prepared by mixing tetraethyl orthosilicate and anhydrous ethanol, and the mass ratio of tetraethyl orthosilicate to anhydrous ethanol is 3.8:15.7;

[0093] The modified liquid 2 is prepared by mixing sorbitan trioleate and 18wt% ethanol solution, and the mass ratio of sorbitan trioleate to 18wt% ethanol solution is 0.2:3.6;

[0094] d. Compound

[0095] 3.7g of modified graphene was placed in 20g of metal composite liquid, the temperature was raised to 30°C, and stirred for 35min. After the stirring was completed, homogenization was performed, the homogenization pressure was 3.4MPa, the homogenization time was 4.0min, and the homogenization times were 3 times. After the homogenization was completed, the temperature was raised to 57°C and stirred for 3.8h. After the stirring was completed, the mixture was separated and dried, and then placed in a calcination furnace for calcination. The temperature was raised to 254°C at a rate of 4.7°C / min, and the mixture was kept at the temperature for calcination for 18min. The temperature was then raised to 506°C at a rate of 3.0°C / min, and the mixture was kept at the temperature for calcination for 4.0h. After the calcination was completed, the temperature was naturally lowered to room temperature to obtain a catalyst.

[0096] The metal composite liquid is a mixed liquid of magnesium citrate, zirconium chloride and deionized water, and the mass ratio of the magnesium citrate, zirconium chloride and deionized water is 4.4:5.0:100.

[0097] 2. Depolymerization reaction

[0098] The polycondensation reactant is fed into a depolymerization device 1 fixed with a catalyst, the depolymerization device 1 is a stirred tank device, the depolymerization temperature is controlled to be 238°C, the vacuum degree is 992Pa, after the material is depolymerized by 85%, the depolymerized material obtained by depolymerization is fed to the purification system, the undepolymerized oligomers are transported to the polycondensation device, 100wt% L-lactic acid is continuously added to the polycondensation device, the amount of L-lactic acid added is 85% of the mass of L-lactic acid in the polycondensation reaction step, and mixed with the undepolymerized oligomers returned to the polycondensation device, the temperature is controlled to be 117°C, the vacuum degree is 7960Pa, a polycondensation reaction is carried out, the time of the first polycondensation reaction is 1.8h, after the first polycondensation reaction is completed, the polycondensation device is heated to 156°C at a rate of 0.8°C / min, the vacuum degree is controlled to be 2980Pa, a secondary polycondensation reaction is carried out, the time of the secondary polycondensation reaction is 3.3h, and the second polycondensation reaction is completed;

[0099] The catalyst used in the depolymerization reaction is the same as the catalyst in the polycondensation reaction step, and the amount used is 0.55% of the dry weight of the L-lactic acid in the polycondensation reaction step.

[0100] 3. Purification

[0101] The depolymerized material obtained after depolymerization is fed to a purification system, and the purification method is distillation purification. The bottom temperature of the distillation device is controlled to be 157° C., the vacuum degree is 495 Pa, and the top reflux ratio is 1:2. The side-drawn product is cooled and granulated to obtain a polymerization-grade lactide product;

[0102] During the distillation and purification process, light components such as water, lactic acid, and M-lactide are discharged from the top of the tower. They can be returned to the polycondensation device and mixed with lactic acid to continue the polycondensation reaction, or they can be recycled separately.

[0103] 4. Post-processing

[0104] After the polycondensation device and the depolymerization device have been running continuously for one week, the residue is discharged once, and the residue enters the degradation device for degradation. The degradation device is a falling film device. Nitrogen is filled for protection during the degradation process. The temperature is controlled at 200°C under normal pressure, the stirring speed is 76rpm, and the degradation time is 1.2h. After the degradation step is completed, the device is transferred to the depolymerization device 2 for depolymerization. The depolymerization device 2 is a stirred tank device. The depolymerization temperature is controlled at 238°C and the pressure is 992Pa. The depolymerized material obtained by depolymerization in the depolymerization device 2 is cooled, mixed with the depolymerized material obtained by depolymerization in the depolymerization device 1, purified, and the remaining residue is discharged.

[0105] The lactide product was prepared by the method of Example 2, and the lactide yield was 99.67%, the free acid mass content in the lactide product was 0.022%, the water mass content was 0.018%, and the lactide mass content was 99.885%.

[0106] Example 3

[0107] 1. Polycondensation

[0108] 100 wt% L-lactic acid is added to a polycondensation device fixed with a catalyst, the polycondensation device is a stirred tank reactor, the temperature of the polycondensation device is raised to 122°C, the vacuum degree is controlled to be 8040Pa, a polycondensation reaction is carried out, the time of the first polycondensation reaction is 2.2 hours, after the first polycondensation reaction is completed, the temperature of the polycondensation device is raised to 163°C at a rate of 1.3°C / min, the vacuum degree is controlled to be 3020Pa, a secondary polycondensation reaction is carried out, the time of the secondary polycondensation reaction is 2.8 hours, after the secondary polycondensation reaction is completed, a polycondensation reactant is obtained;

[0109] The amount of the catalyst added is 0.60% of the dry mass of L-lactic acid;

[0110] The method for preparing the catalyst comprises the following steps:

[0111] a. Graphene pretreatment

[0112] 8.4 g of graphene was placed in 80 g of 25 wt% nitric acid solution for ultrasonic dispersion treatment, the ultrasonic time was 28 min, the ultrasonic power was 184 W, and the ultrasonic frequency was 32 kHz. After the ultrasonic dispersion was completed, the temperature was raised to 67 ° C, stirred at 260 rpm for 3.2 h, filtered out and washed, and dried at 88 ° C for 5.8 h to obtain pretreated graphene;

[0113] The particle size of the graphene is 140 nm;

[0114] b. Distributed processing

[0115] 7.7 g of pretreated graphene was placed in 105 g of 28 wt% ethanol solution, 0.77 g of lauryl amide propyl amine oxide was added, the temperature was raised to 57° C. and stirred, the stirring speed was controlled to 326 rpm, the stirring time was 1.5 h, after the stirring was completed, 11.5 g of 2,6-diaminopyridine was added, the temperature was raised to 84° C. at a rate of 1.4° C. / min, the mixture was kept warm and stirred for 4.6 h, and then 10.3 g of L-glutamine was added, the mixture was kept warm and stirred for 4.8 h, and dispersed graphene was obtained after the stirring was completed;

[0116] c. Modification treatment

[0117] 4.4 g of dispersed graphene was placed in 132 g of 22 wt% ethanol solution, and after stirring evenly, the temperature was raised to 38° C., 20.3 g of modified liquid 1 was added at a speed of 510 rpm, and the addition rate of modified liquid 1 was controlled to be 0.54 g / min. After the addition was completed, the reaction was kept warm for 33 min, 24 wt% ammonia water was added to adjust the pH to 9.2, and then 4.2 g of modified liquid 2 was added, and the addition rate of modified liquid 2 was controlled to be 0.27 g / min. After the addition was completed, the reaction was continued to stir for 24.5 h, centrifuged, washed, and dried at -42° C. for 9 h to obtain modified graphene;

[0118] The modified liquid 1 is prepared by mixing tetraethyl orthosilicate and anhydrous ethanol, and the mass ratio of tetraethyl orthosilicate to anhydrous ethanol is 4.2:16.4;

[0119] The modified liquid 2 is prepared by mixing sorbitan trioleate and 22wt% ethanol solution, and the mass ratio of sorbitan trioleate to 22wt% ethanol solution is 0.2:4.1;

[0120] d. Compound

[0121] 4.3 g of modified graphene was placed in 26 g of metal composite liquid, the temperature was raised to 35° C., and stirred for 43 min. After the stirring was completed, homogenization was performed, the homogenization pressure was 3.7 MPa, the homogenization time was 5.0 min, and the homogenization times were 3 times. After the homogenization was completed, the temperature was raised to 62° C. and stirred for 4.4 h. After the stirring was completed, the mixture was separated and dried, and then placed in a calcination furnace for calcination. The temperature was raised to 265° C. at a rate of 5.3° C. / min, and the mixture was kept at the temperature for calcination for 23 min. The temperature was then raised to 513° C. at a rate of 3.5° C. / min, and the mixture was kept at the temperature for calcination for 4.5 h. After the calcination was completed, the temperature was naturally lowered to room temperature to obtain a catalyst.

[0122] The metal composite liquid is a mixed liquid of magnesium citrate, zirconium chloride and deionized water, and the mass ratio of the magnesium citrate, zirconium chloride and deionized water is 4.8:5.3:100.

[0123] 2. Depolymerization reaction

[0124] The polycondensation reactant is fed into a depolymerization device 1 fixed with a catalyst, the depolymerization device 1 is a falling film device, the depolymerization temperature is controlled to be 242°C, the vacuum degree is 1000Pa, after the material is depolymerized 85%, the depolymerized material obtained by the depolymerization is fed into the purification system, the undepolymerized oligomers are transported to the polycondensation device, 100wt% L-lactic acid is continuously added to the polycondensation device, the amount of L-lactic acid added is 90% of the mass of L-lactic acid in the polycondensation reaction step, and mixed with the undepolymerized oligomers returned to the polycondensation device, the temperature is controlled to be 122°C, the vacuum degree is 8040Pa, a polycondensation reaction is carried out, the time of the first polycondensation reaction is 2.2h, after the first polycondensation reaction is completed, the polycondensation device is heated to 163°C at a rate of 1.3°C / min, the vacuum degree is controlled to be 3020Pa, a secondary polycondensation reaction is carried out, the time of the secondary polycondensation reaction is 2.8h, and the second polycondensation reaction is completed;

[0125] The catalyst used in the depolymerization reaction is the same as the catalyst in the polycondensation reaction step, and the amount used is 0.60% of the dry mass of the L-lactic acid in the polycondensation reaction step.

[0126] 3. Purification

[0127] The depolymerized material obtained after depolymerization is fed to a purification system, and the purification method is distillation purification. The bottom temperature of the distillation device is controlled to be 162°C, the vacuum degree is 503Pa, and the top reflux ratio is 1:2. The side-drawn product is cooled and granulated to obtain a polymerization-grade lactide product;

[0128] During the distillation and purification process, light components such as water, lactic acid, and M-lactide are discharged from the top of the tower. They can be returned to the polycondensation device and mixed with lactic acid to continue the polycondensation reaction, or they can be recycled separately.

[0129] 4. Post-processing

[0130] After the polycondensation device and the depolymerization device have been running continuously for one week, the residue is discharged once and the residue enters the degradation device for degradation. The degradation device is a scraping film device. Nitrogen is filled for protection during the degradation process. The temperature is controlled to be 206°C under normal pressure, the stirring speed is 83rpm, and the degradation time is 0.9h. After the degradation step is completed, the residue is transferred to the depolymerization device 2 for depolymerization. The depolymerization device 2 is a falling film device. The depolymerization temperature is controlled to be 242°C and the pressure is 1000Pa. The depolymerized material obtained by depolymerization in the depolymerization device 2 is cooled and mixed with the depolymerized material obtained by depolymerization in the depolymerization device 1 for purification, and the remaining residue is discharged.

[0131] The lactide product was prepared by the method of Example 3, and the lactide yield was 99.73%. The free acid mass content in the lactide product was 0.020%, the water mass content was 0.017%, and the lactide mass content was 99.892%.

[0132] Comparative Example 1

[0133] Based on Example 1, the changes are as follows:

[0134] In the method for preparing the catalyst for the polycondensation reaction step, the dispersion treatment step is omitted;

[0135] In the modification step, dispersed graphene is replaced by pretreated graphene in equal amounts;

[0136] The rest of the operations are the same.

[0137] The method of Comparative Example 1 was used to prepare a lactide product, and the comprehensive yield of lactide was 96.14%, the free acid mass content in the lactide product was 0.328%, the water mass content was 0.026%, and the lactide mass content was 96.002%.

[0138] Comparative Example 2

[0139] Based on Example 1, the changes are as follows:

[0140] (1) In the preparation method of the catalyst in the polycondensation reaction step, the modification treatment step is omitted; in the compounding step, the modified graphene is replaced by dispersed graphene in equal amounts;

[0141] (2) In the depolymerization reaction step, the depolymerized material obtained after depolymerization is fed to the purification system, and the undepolymerized oligomers are directly discharged, that is, "the undepolymerized oligomers and the catalyst are transported to the polycondensation device, ... the time for the secondary polycondensation reaction is 3.0 hours, and the secondary polycondensation reaction is completed" is omitted;

[0142] The rest of the operations are the same.

[0143] The method of Comparative Example 2 was adopted to prepare a lactide product, and the comprehensive yield of lactide was 94.22%, the free acid mass content in the lactide product was 0.537%, the water mass content was 0.031%, and the lactide mass content was 95.355%.

[0144] Catalyst stability performance test

[0145] The catalysts prepared in Examples 1-3 and Comparative Examples 1-2 were used to perform a catalyst stability test. Specifically, the catalysts prepared in Examples 1-3 and Comparative Examples 1-2 were respectively used to perform continuous production according to the preparation method of lactide in Example 1. The continuous production time was 960 hours. The yield of the lactide product, as well as the lactide content, free acid content and moisture content in the lactide product were tested again. The specific results are as follows:

[0146]

[0147] The present invention adopts a specific method to prepare a catalyst, using graphene as a catalyst carrier, dispersing the graphene, wherein 2,6-diaminopyridine can be grafted onto the graphene surface, and L-glutamine can also be reacted and connected with 2,6-diaminopyridine, thereby expanding the interlayer spacing of the graphene and enhancing the dispersion performance of the graphene, which is more conducive to the loading of active metals and improving the catalytic activity. In the modification step, silicon dioxide and the dispersed graphene are polymerized in situ, combined with the composite step, the stability of the catalyst is enhanced, and the catalytic activity and long-lasting catalytic performance are guaranteed; at the same time, in the depolymerization step, the same catalyst as in the polycondensation step is used, and the depolymerized product obtained after depolymerization is completed. The material is purified to obtain the lactide product, which improves the purity and yield of the lactide product and reduces the impurities and moisture content; the undepolymerized material is returned to the polycondensation device to react with lactic acid again, so that the molecular weight of the higher molecular weight polymer is rearranged by reacting with lactic acid, and the molecular weight is reduced, which is conducive to the smooth depolymerization at the subsequent temperature; before the intermittent residue discharge, the oligomers with a higher degree of polymerization are properly degraded under nitrogen protection to reduce the degree of polymerization of the polymer in the residue, and subsequent depolymerization is carried out to further improve the lactide yield, and then the residue is discharged, which improves the raw material utilization rate and the total yield of lactide, reduces the production cost of lactide, improves the product purity, and reduces the discharge amount.

[0148] In the catalyst preparation method of Comparative Example 1, the dispersion treatment step is omitted, and the pretreated graphene is directly used for modification treatment. The interlayer spacing of the pretreated graphene is small and the dispersibility is poor. In the modification treatment step, the in situ polymerization of silica and the pretreated graphene is poor, resulting in a small loading amount of active metals, unstable loading, and poor loading performance, which reduces the catalytic activity and catalytic stability of the catalyst, ultimately reducing the yield and purity of the product and increasing the content of by-products.

[0149] In the depolymerization step of Comparative Example 2, the step of returning the undepolymerized oligomers to the polycondensation device for another polycondensation reaction with lactic acid is omitted. The undepolymerized oligomers are directly discharged without recycling the oligomers, resulting in low raw material utilization, greatly reducing the product yield and purity, and limiting the use of the lactide product. In addition, in the method for preparing the catalyst in Comparative Example 2, the modification treatment is omitted, that is, the in-situ polymerization of silica and dispersed graphene is omitted, which affects the activity and stability of the catalyst, resulting in poor catalytic performance for the reaction. In the continuous catalytic process, the catalytic ability is greatly weakened, and the catalytic durability is poor.

[0150] Unless otherwise specified, all percentages used in the present invention are by mass.

[0151] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing lactide, characterized in that: It includes polycondensation reaction, depolymerization reaction, purification and post-processing steps; The polycondensation reaction step comprises placing L-lactic acid and a catalyst in a polycondensation device for a polycondensation reaction, raising the temperature to 117-122° C., controlling the vacuum degree to 7960-8040 Pa, performing a polycondensation reaction for 1.8-2.2 hours, and after the first polycondensation reaction is completed, raising the temperature to 156-163° C. at a rate of 0.8-1.3° C. / min, controlling the vacuum degree to 2980-3020 Pa, performing a secondary polycondensation reaction for 2.8-3.3 hours, and obtaining a polycondensation reactant after the secondary polycondensation reaction is completed; The preparation method of the catalyst includes graphene pretreatment, dispersion treatment, modification treatment and compounding steps; The graphene pretreatment step comprises placing the graphene in a nitric acid solution for ultrasonic dispersion treatment, wherein the ultrasonic time is 23-28 minutes, the ultrasonic power is 175-184W, and the ultrasonic frequency is 28-32kHz. After the ultrasonic dispersion is completed, the temperature is increased to 62-67°C, and the mixture is stirred at 240-260rpm for 2.7-3.2h. After filtering and washing, the mixture is dried at 83-88°C for 5.8-6.2h to obtain the pretreated graphene. The step of the dispersion treatment is to place the pretreated graphene in an ethanol solution, add lauramide propylamine oxide, raise the temperature to 52-57°C for stirring, control the stirring speed to 310-326rpm, and stir for 1.0-1.5h. After the stirring is completed, add 2,6-diaminopyridine, raise the temperature to 80-84°C at a rate of 0.7-1.4°C / min, keep warm and stir for 4.3-4.6h, then add L-glutamine, keep warm and stir for 4.3-4.8h, and obtain dispersed graphene after the stirring is completed; The modification treatment step is to place the dispersed graphene in an ethanol solution, stir evenly, raise the temperature to 33-38°C, add the modification solution 1 at a speed of 488-510rpm, keep the temperature for reaction for 27-33min after the addition is completed, add ammonia water to adjust the pH to 9.0-9.2, then add the modification solution 2, continue stirring and reacting for 23.5-24.5h after the addition is completed, centrifuge, wash and dry to obtain the modified graphene; The modified liquid 1 is prepared by mixing tetraethyl orthosilicate and anhydrous ethanol; the modified liquid 2 is prepared by mixing sorbitan trioleate and 18-22wt% ethanol solution; The compounding step comprises placing the modified graphene in a metal composite liquid, raising the temperature to 30-35° C., stirring for 35-43 minutes, performing homogenization after the stirring is completed, raising the temperature to 57-62° C., stirring for 3.8-4.4 hours, separating and drying after the stirring is completed, placing in a calcining furnace for calcining, and waiting for the temperature to naturally decrease to room temperature after the calcination is completed to obtain a catalyst; The metal composite liquid is a mixture of magnesium citrate, zirconium chloride and deionized water, and the mass ratio of the magnesium citrate, zirconium chloride and deionized water is 4.4-4.8:5.0-5.3:100; The depolymerization reaction step comprises feeding the polycondensation reactant into a depolymerization device 1 fixed with a catalyst to carry out a depolymerization reaction, and after 85% of the material is depolymerized, feeding the depolymerized material obtained after the depolymerization is completed into a purification system for purification, and then cooling and granulating to obtain a polymerization-grade lactide product; The depolymerization step further includes transporting the undepolymerized oligomers to a polycondensation device, adding L-lactic acid to the polycondensation device, mixing the L-lactic acid with the undepolymerized oligomers returned to the polycondensation device, and performing polycondensation again.

2. The method for preparing lactide according to claim 1, characterized in that: In the polycondensation reaction step, the mass concentration of L-lactic acid is 100%; The polycondensation device is one of a stirred tank type, a falling film type or a scraped film type reaction device; The added amount of the catalyst is 0.55-0.60% of the dry basis mass of L-lactic acid.

3. The method for preparing lactide according to claim 1, characterized in that: In the graphene pretreatment step, the graphene has a particle size of 120-140 nm; The mass concentration of the nitric acid solution is 22-25%; The mass ratio of the graphene to the nitric acid solution is 8.0-8.4:73-80.

4. The method for preparing lactide according to claim 1, characterized in that: In the step of dispersing, the mass concentration of the ethanol solution is 24-28%; The mass ratio of the pretreated graphene, ethanol solution, lauramide propylamine oxide, 2,6-diaminopyridine and L-glutamine is 7.3-7.7:96-105:0.72-0.77:11.0-11.5:10.0-10.

3.

5. The method for preparing lactide according to claim 1, characterized in that: In the modification step, the mass concentration of the ethanol solution is 17-22%; The mass ratio of the dispersed graphene, the ethanol solution, the modified liquid 1, and the modified liquid 2 is 4.0-4.4:127-132:19.6-20.3:3.8-4.2; In the modified liquid 1, the mass ratio of tetraethyl orthosilicate to anhydrous ethanol is 3.8-4.2:15.7-16.4; In the modified solution 2, the mass ratio of sorbitan trioleate to 18-22wt% ethanol solution is 0.2:3.6-4.1; The addition rate of the modified liquid 1 is 0.50-0.54 g / min, and the addition rate of the modified liquid 2 is 0.22-0.29 g / min; The mass concentration of the ammonia water is 20-24%.

6. The method for preparing lactide according to claim 1, characterized in that: In the compounding step, the mass ratio of the modified graphene to the metal composite liquid is 3.7-4.3:20-26; The homogenization process has a homogenization pressure of 3.4-3.7 MPa, a homogenization time of 4.0-5.0 min, and a homogenization frequency of 3 times; The calcination is firstly to increase the temperature to 254-265°C at a rate of 4.7-5.3°C / min, keep the temperature for 18-23min, then to increase the temperature to 506-513°C at a rate of 3.0-3.5°C / min, keep the temperature for 4.0-4.5h.

7. The method for preparing lactide according to claim 1, characterized in that: In the depolymerization reaction step, the depolymerization device 1 is one of a stirred tank device, a falling film device or a scraped film device; In the depolymerization reaction, the depolymerization temperature is 238-242° C. and the vacuum degree is 992-1000 Pa; The catalyst used in the depolymerization reaction is the same as the catalyst in the polycondensation reaction step, and the amount used is 0.55-0.60% of the dry mass of L-lactic acid in the polycondensation reaction step.

8. The method for preparing lactide according to claim 1, characterized in that: In the step of the depolymerization reaction, the mass concentration of the L-lactic acid is 100wt%; The amount of L-lactic acid added is 85-90% of the mass of L-lactic acid in the polycondensation reaction step; For the polycondensation reaction, the temperature is controlled at 117-122°C and the vacuum degree is 7960-8040Pa, and a polycondensation reaction is carried out for 1.8-2.2h. After the polycondensation reaction is completed, the temperature is raised to 156-163°C at a rate of 0.8-1.3°C / min, and the vacuum degree is controlled at 2980-3020Pa, and a secondary polycondensation reaction is carried out for 2.8-3.3h.

9. The method for preparing lactide according to claim 1, characterized in that: The purification step is to feed the depolymerized material obtained after depolymerization into a purification system, and the purification method is distillation purification, the bottom temperature of the distillation device is controlled to be 157-162°C, the vacuum degree is 495-503Pa, and the top reflux ratio is 1:2, and the side-extracted product is cooled and granulated to obtain a polymerization-grade lactide product; During the distillation and purification process, light components such as water, lactic acid, and M-lactide are discharged from the top of the tower. They can be returned to the polycondensation device and mixed with lactic acid to continue the polycondensation reaction, or they can be recycled separately.

10. The method for preparing lactide according to claim 1, characterized in that: The post-treatment step is as follows: after the polycondensation device and the depolymerization device have been operated continuously for one week, the residue is discharged once, and the residue enters the degradation device for degradation. During the degradation process, nitrogen is filled for protection, the temperature is controlled at 200-206° C. under normal pressure, the stirring speed is 76-83 rpm, and the degradation time is 0.9-1.2 h. After the degradation step is completed, the residue is transferred to the depolymerization device 2 for depolymerization, the depolymerization temperature is controlled at 238-242° C., and the pressure is 992-1000 Pa. After the depolymerization is completed in the depolymerization device 2, the depolymerized material is cooled, mixed with the depolymerized material obtained by the depolymerization in the depolymerization device 1, purified, and the remaining residue is discharged; The degradation device is one of a kettle stirring device, a falling film device or a scraping film device; The depolymerization device 2 is one of a stirred tank device, a falling film device or a scraped film device.

Citation Information

Patent Citations

  • Catalyst for preparing lactides from lactic acid and method for preparing lactides from lactic acid

    CN109894109A

  • Recrystallization process of refined lactide

    CN111961028A